A Criminal Study Responsibility Of Cybercrime Perpetrators According To Law Number 11 Of 2008 Concerning Electronic Information and Transactions - Wahyu Dwi Saputra; Desy Maryani; Sandi Aprianto (Utami Publisher, 2026)
The development of information and communication technology has had a significant impact on people's lives, particularly with the emergence of various forms of cybercrime. Cybercrime has characteristics that differ from conventional crime, including being committed through electronic systems, being cross-border, and using digital data and information as both a means and object of the crime. These conditions demand the existence of criminal law regulations that can provide legal certainty and protect the legal interests of the community in cyberspace. Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE) is present as a legal instrument to regulate criminal acts in the field of information technology, including regulations regarding the criminal liability of perpetrators of cybercrime. This study aims to examine the provisions on criminal liability of perpetrators of cybercrime under the ITE Law and analyze the obstacles faced in its implementation. The research method used is normative legal research with a statutory approach, a conceptual approach, and a case approach. The legal materials used include primary, secondary, and tertiary legal materials analyzed qualitatively. The research results show that the provisions on criminal liability in the ITE Law are fundamentally based on the principle of fault (geen straf zonder schuld) and recognize a broad range of legal subjects, including individuals and corporations. The ITE Law also regulates various forms of cybercrime and their associated criminal sanctions. However, in practice, various obstacles remain, including the difficulty of obtaining electronic evidence, the limited capacity of law enforcement officials, the transnational nature of cybercrime, and the potential for multiple interpretations of several provisions of the ITE Law. Therefore, regulatory strengthening, capacity building of law enforcement officials, and strengthening international cooperation and public digital literacy are needed to achieve effective and equitable cybercrime law enforcement.